An unusual case of gestational diabetes mellitus. Issue 923 (1st September 2002) - Shankar, P; Sundarka, M K; Sundarka, A
Abstract : The case of a woman, who developed gestational diabetes at six weeks in two successive pregnancies, is reported. She was in the high risk group to develop gestational diabetes. The first pregnancy terminated in abortion at 10 weeks. In the second pregnancy, institution of insulin therapy at diagnosis was associated with a successful outcome. This case highlights the need for screening for gestational diabetes at the first antenatal visit in the high risk group.